Efficacy of 1060 nm Diode Laser for Non-Invasive Subcutaneous Fat Reduction in Mini-Pigs - Lee YJ; Hong N; Choi ES; Choi SH; Kim EY; Park HJ; Ahn JC (Dove Medical Press, 2024)
Yea-Jin Lee,1,2 Namgue Hong,2 Eun Seo Choi,3 Sun-Hyang Choi,2 Eun Young Kim,2 Hyeong Ju Park,4 Jin-Chul Ahn1,2 1Department of Medicine, Dankook University, Cheonan-si, 31116, Republic of Korea; 2Medical Laser Research Center, Graduate School of Medicine, Dankook University, Cheonan-si, 31116, Republic of Korea; 3Department of Physics, Chosun University, Gwangju, 61452, Republic of Korea; 4Bio&Health Photonics Research Center, Korea Photonics Technology Institute, Gwangju, 61007, Republic of KoreaCorrespondence: Hyeong Ju Park; Jin-Chul Ahn, Email phj020603@kopti.re.kr; jcahn@dankook.ac.krPurpose: To evaluate the efficacy and safety of abdominal fat reduction in mini-pigs, utilizing at 1060 nm diode laser with a wavelength of 1060 nm.Patients and Methods: The laser system non-invasively disrupts adipose tissue; its effectiveness and safety were evaluated by ultrasound imaging and histological analysis. Laser irradiation was performed with various powers, and the cooling function was activated to prevent skin surface damage.Results: The dermal tissue temperature increased to at least 43°C during laser exposure, leading to a decrease in abdominal fat thickness after 30 days. Blood tests revealed no significant changes in kidney and liver function but showed increased blood levels of nonessential free acids (NEFAs), likely due to the release of fatty tissue-derived free fatty acids. Histological evaluation demonstrated rapid transformation of adipose tissue into collagen, muscle fibers, and intracellular fibrous tissue.Conclusion: The 1060 nm laser showed promise as a non-invasive and safe tool for reducing abdominal fat.Keywords: diode laser, fat, abdominal, non-invasive, preclinical